2009
DOI: 10.1007/s10549-009-0409-y
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided detection in full-field digital mammography in a clinical population: performance of radiologist and technologists

Abstract: The purpose of the study was to evaluate the impact of a computer-aided detection (CAD) system on the performance of mammogram readers in interpreting digital mammograms in a clinical population. Furthermore, the ability of a CAD system to detect breast cancer in digital mammography was studied in comparison to the performance of radiologists and technologists as mammogram readers. Digital mammograms of 1,048 consecutive patients were evaluated by a radiologist and three technologists. Abnormalities were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Our results are similar to those of others who have looked at the sensitivity of CAD with digital mammography [6, 1316], finding no difference in radiologists’ performance with and without CAD overall. Four of 14 readers (28.6%) achieved significant improvement in sensitivity with the iCAD system, and four of 15 readers (26.7%) achieved significant improvement in sensitivity with the R2 system.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are similar to those of others who have looked at the sensitivity of CAD with digital mammography [6, 1316], finding no difference in radiologists’ performance with and without CAD overall. Four of 14 readers (28.6%) achieved significant improvement in sensitivity with the iCAD system, and four of 15 readers (26.7%) achieved significant improvement in sensitivity with the R2 system.…”
Section: Discussionsupporting
confidence: 91%
“…Although CAD was in widespread use in the United States by 2008, opinions expressed in articles published since remain mixed on the impact of this technology on radiologist performance in the detection of breast cancer [46]. Given the low sensitivity to breast cancers on both film-screen (0.41) and digital (0.41) mammography in DMIST [2] and the results of stand-alone assessment of the sensitivity of the two CAD systems, iCAD (0.74) and R2 (0.74), to cancers in DMIST (including interval cancers and those found at 1-year follow-up) [7], we anticipated that application of CAD to the challenging screening cases in DMIST should result in improved radiologist per formance.…”
mentioning
confidence: 99%
“…One study reported the usage of a CAD system for mammogram reading by a radiologist and three technologists, and concluded the CAD system failed to improve performance of either the radiologist or the three technologists [20]. Another study evaluated the efficacy of a CAD system for low-dose CT lung cancer screening, and found the detection accuracy improved significantly for thoracic and general radiologists using the CAD system; however, no statistically significant difference in the diagnostic accuracy obtained with and without the use of CAD was seen for residents [21].…”
Section: Discussionmentioning
confidence: 99%
“…Logically, the use of CAD systems that have superb sensitivity for the detection of malignant microcalcifications seems to be very attractive in digital mammography. Previous studies [12,[17][18][19] have shown that CAD sensitivity for the detection of breast cancer is similar in fatty breasts and dense breasts in both SFM [17] and FFDM [20][21][22][23]; however, indirect-CAD sensitivity for subgroups of cancers apparent only as microcalcifications has been shown to be higher in dense breasts than the sensitivity for calcifications in fatty breasts [12]. The indirect-CAD sensitivity was markedly lower in cases of malignant amorphous calcifications than in other malignant calcifications [12].…”
Section: Discussionmentioning
confidence: 92%